Kelebihan Penduduk dan Konsumsi Berlebihan dalam Kasus Krisis Air Dunia - Ainun Jariah (Millah: Journal of Religious Studies, 2007)
Amount of earthling in this time reach 6,6 billion growth level 76 million per year. According  to United Nation amount of resident of earth will increase counted 2,6 billion in 2050. Care  problem of excess of resident early when natural resources and environment star to destroy.  Beside height growth of resident amount, pattern consume abundant human being result earth  natural resources pressure mount also. This matter because of amount of higher resident as  whole compared to ability of earth fulfill requirement of consumption resident of earth so that  growth of high resident and also consumption which is abundant to be considered to be root  problems of environment, among others irrigate crisis world. Irrigate crisis happened because of  unconscious of human being will total up limited water and also increasing it is amount of  human being owning is same requirement to water. Islam is one of the big religion in the world  has important role in solving environment problem, that is with studying about ethical respon of  Islam to clean water and proprietary rights irrigate as natural resource wich provide by nature.  Inequal access clean water because of lack of awareness of human being will total up available under the sun water.